2022
DOI: 10.1002/ange.202212770
|View full text |Cite
|
Sign up to set email alerts
|

Di‐2,7‐pyrenidecaphyrin(1.1.0.0.0.1.1.0.0.0) and Its Bis‐Organopalladium Complexes: Synthesis and Chiroptical Properties

Abstract: A non-aromatic expanded carbaporphyrinoid, incorporating two built-in 2,7-pyrenylene moieties was synthesized. The intrinsically labile structure was demonstrated by proton-triggered conformational changes between the figure-of-eight and quasi-Möbius conformers. Upon treatment with Pd(OAc) 2 , the reaction produces two bis-Pd II complexes with distinct coordination modes. Metal coordination serves to fix the macrocyclic frameworks with the net result that both bis-Pd II complexes could be resolved by high perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 86 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…They have attracted interest for their π-conjugation pathways that differ from those of traditional tetrapyrrolic porphyrins as well as their own unique metal coordination chemistry. To date, polycyclic aromatic hydrocarbons (PAHs), such as naphthalene, anthracene, phenanthrene, triphenylene, and pyrene, have been used to create carbaporphyrins. Recently, we reported that dibenzo­[ g , p ]­chrysene could serve as a building block to prepare a bis-dicarbacorrole, a highly twisted three-dimensional (3-D) cage structure, and a pyrene-containing belt-like system. However, to the best of our knowledge, large π-extended PAHs, such as nanographenes, have yet to be introduced into carbaporphyrin frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…They have attracted interest for their π-conjugation pathways that differ from those of traditional tetrapyrrolic porphyrins as well as their own unique metal coordination chemistry. To date, polycyclic aromatic hydrocarbons (PAHs), such as naphthalene, anthracene, phenanthrene, triphenylene, and pyrene, have been used to create carbaporphyrins. Recently, we reported that dibenzo­[ g , p ]­chrysene could serve as a building block to prepare a bis-dicarbacorrole, a highly twisted three-dimensional (3-D) cage structure, and a pyrene-containing belt-like system. However, to the best of our knowledge, large π-extended PAHs, such as nanographenes, have yet to be introduced into carbaporphyrin frameworks.…”
Section: Introductionmentioning
confidence: 99%